DINGS SKILLS WAIST IN WRESTLING SPORTS (The Experimental Study Effects of Training Methods and Power for Students at FIK UNM) - Juhanis, J (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
This experimental research aims to determine the effect of exercise and power against dings waist wrestling skills. Research conducted at the State FIK University of Makassar. Experimental method using a 2x3 factorial design. Samples 66 students. The data analysis technique is the analysis of variance and Tukey test. The results showed that (1) Method of exercise resistance band higher influence of the training methods good morning to a skill dings waist, (2) Method of exercise resistance band higher influence of the training methods bicep curl to a skill dings waist, (3) Method of exercise good morning higher influence of the training methods bicep curl to a skill dings waist, (4) There is interaction between the practice and power against skills dings waist, (5) method of exercise resistance band higher than a method practice good morning to a skill dings waist high power, (6) method of exercise resistance band higher than a method practice good morning to a skill dings waist high power, (7) method of exercise good morning higher of the training methods bicep curl to a skill dings waist high power, (8) method of exercise resistance band more height of the training methods good morning to a skill dings waist low power, (9) method of exercise resistance band higher than a method practice good morning to a skill dings waist low power, and (10) method of exercise good morning higher of the training methods bicep curl against low power waist dings skills.